Seismotectonic Characteristics of the Northern Sector of the Banda Arc Based on Spatiotemporal Analysis of b-Values and Focal Mechanisms - Rahmatun Inayah; Ika Umratul Asni Aminy; Kormil Saputra (Jurnal Geosains West Science, 2026)
The seismotectonic activity in the Northern Sector of the Banda Arc is highly active and destructive, as evidenced by historical earthquakes dating back to 1674, including the 2023 Banda Sea earthquake. This study aims to evaluate seismotectonic dynamics both spatially and temporally, providing an overview of seismic risk in the region. The novelty of this study lies in the vertical stratification analysis of -values and focal mechanism parameters utilizing an earthquake catalog updated through March 2026. The seismotectonic evaluation was conducted by analyzing the temporal -values over a 26-year observation period using the Maximum Likelihood Estimation (MLE) method. Spatial b-value analysis was performed on the Seram and Buru segments, along with vertical stratification in the shallow (0-35 km) and deep (35-100 km) layers. The study results indicate that the shallow layer acts as the primary zone of stress accumulation (< 1.0), whereas the deep layer is in a relaxation phase ( > 1.4). Focal mechanism analysis confirms that stress accumulation in the shallow zone is driven by a Northeast–Southwest compressive force, which is released periodically through a combination of local thrust and strike-slip faulting. The Buru segment is identified as being under critical tectonic vulnerability due to a consistent decrease in b-values ​​to 0.87 without a significant relaxation phase. The implications of this research include increased periodic seismic monitoring and strengthening of both structural and non-structural disaster mitigation programs in the Central Maluku region, particularly in Buru Island.